2021
DOI: 10.1177/10664807211063197
|View full text |Cite
|
Sign up to set email alerts
|

Coresidence is Not a Failure to Launch or Boomerang Children

Abstract: Literature on emerging adults living with their parents has presented this concept as a problem and emphasized a White European-North American or individualistic voice through the use of terms such as “failure to launch” or “boomerang” children. The authors highlight an alternative term, coresidence, and perspectives from collectivistic cultures outside of the dominant view that have historically been marginalized and underrepresented in research. A case study of the first author's lived experiences as a repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The academic literature and print media use a variety of terms to describe this living arrangement. Terms such as boomerang kids (Yu, 2022), failure to launch (Bell et al, 2007), and stuck in the nest (Mazurik et al, 2020; Rampell, 2011) tend to reflect a more critical stance, while the use of the term coresidence reflects a neutral (White & Rogers, 1997) or culturally sensitive perspective (Evans et al, 2022 ). Recent survey data and print media indicate that this living arrangement is increasingly common among 20–34-year-olds (Fry, 2017; Fry et al, 2020 ) and has, consequently, become a more desirable option for young adults (Parker, 2012; Pinsker, 2020) and a less stigmatized experience for parents (Casares & White, 2018; Khan, 2021; Weale, 2018).…”
Section: Case Study Respondent: D Robert Casares Jr Phd Lcmhc Lpc Nccmentioning
confidence: 99%
“…The academic literature and print media use a variety of terms to describe this living arrangement. Terms such as boomerang kids (Yu, 2022), failure to launch (Bell et al, 2007), and stuck in the nest (Mazurik et al, 2020; Rampell, 2011) tend to reflect a more critical stance, while the use of the term coresidence reflects a neutral (White & Rogers, 1997) or culturally sensitive perspective (Evans et al, 2022 ). Recent survey data and print media indicate that this living arrangement is increasingly common among 20–34-year-olds (Fry, 2017; Fry et al, 2020 ) and has, consequently, become a more desirable option for young adults (Parker, 2012; Pinsker, 2020) and a less stigmatized experience for parents (Casares & White, 2018; Khan, 2021; Weale, 2018).…”
Section: Case Study Respondent: D Robert Casares Jr Phd Lcmhc Lpc Nccmentioning
confidence: 99%
“…Adding important nuance, Evans et al (2021) argued that negative attitudes toward coresidence are closely tied to the individualistic values that dominate White European and North American cultural spaces. They noted that while White Americans frequently position coresidence as a "failure to launch" (p. 459), Americans from more collectivist backgrounds frequently support, normalize, and celebrate young adult and parent coresidence.…”
Section: Attitudes Toward Coresidencementioning
confidence: 99%
“…Speaking to how individual circumstances can impact moral judgements, studies have also found that attitudes toward coresidence vary according to the motivations and circumstances of the coresiding young adult. Though neither Canadians nor Americans have typically considered coresidence an ideal or preferable living situation for young adults (Evans et al, 2021; Mitchell & Lennox, 2020; Seltzer et al, 2012), this arrangement has been acceptable when the young adult is actively working toward financial and residential independence. Consistent with this, attitudes toward coresidence have been more favorable when temporary or short-term than indefinite (Mitchell & Lennox, 2020; Seltzer et al, 2012).…”
Section: Coresidence In Western Society and Mediamentioning
confidence: 99%